Salivary microbiome in peritoneal dialysis patients with and without sarcopenia: A pilot study - Wararak Choovanichvong; Sirirak Supa-Amornkul; Dulyapong Rungraungrayabkul; Natcha Boonyapratheeprat; Sasiwimon Meenetkum; Sarinya Boongird; Piyatida Chuengsaman; Chagriya Kitiyakara; Sujiwan Seubbuk Sangkhamanee (PLoS ONE, 2025)
Purpose To investigate salivary microbiota composition in end-stage kidney disease (ESKD) patients with sarcopenia (SESKD), ESKD patients without sarcopenia (NSESKD), and individuals without chronic kidney disease (control group). Materials and Methods Thirty-three participants were enrolled: 10 SESKD patients, 12 NSESKD patients, and 11 controls. Demographic data, oral examinations, and unstimulated saliva samples were collected. Salivary bacterial microbiomes were analyzed using high-throughput sequencing targeting the V3-V4 region of the bacterial 16S rRNA gene. Results The overall bacterial abundance and distribution were significantly higher in the SESKD and NSESKD groups compared to the control group (p < 0.05), with no significant differences between the SESKD and NSESKD groups. ESKD, educational level, and muscle strength were significantly associated with variations in the salivary microbiome composition. Analysis of bacterial abundance revealed a shift in trends as the disease combined from control to NSESKD and SESKD group, respectively, across 7 genera: Actinobacillus, TM7x, Capnocytophaga, Neisseria, and Leptotrichia increased in abundance, while Actinomyces and Atopobium decreased. Linear discriminant analysis effect size (LEfSe) identified Leptotrichia as a potential biomarker for ESKD (both with and without sarcopenia). Conclusion ESKD condition impacted microbial composition, with minimal influence from sarcopenia. Specifically, Leptotrichia was notably higher in the ESKD group.